2021
DOI: 10.1002/solr.202100911
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Interface Passivation Strategies for Sb2Se3/CdS Solar Cells

Abstract: Sb2Se3 is an emerging earth‐abundant material praised for its promising optoelectronic properties, although the presence of interfacial defects at the vicinity of the p–n junction limit its performance as photovoltaic absorber. Using a device modeling approach and a realistic set of material parameters, it unravels pathways mitigating the impact of interfacial defects with a baseline Sb2Se3/CdS. Two straightforward strategies are devised and tested against the baseline. First, a thin front surface sulfurizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To test the hypothesis of a buried homojunction following KCN etching, we conducted numerical simulations investigating the influence of an ultrathin n-doped layer on the surface of the absorber in a SCAPS-1D model, building upon the previously reported baseline that simulates the behavior of Sb 2 Se 3 . 18 We varied the doping level of the n-type surface layer from 10 13 to 10 19 cm –3 and the doping depth from 2 to 20 nm, while keeping other parameters constant, including the interface defect properties. As the exact characteristics of this doping layer are currently unknown, we performed a parametric variation of both doping level and depth simultaneously to create surface plots for each photovoltaic figure of merit.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test the hypothesis of a buried homojunction following KCN etching, we conducted numerical simulations investigating the influence of an ultrathin n-doped layer on the surface of the absorber in a SCAPS-1D model, building upon the previously reported baseline that simulates the behavior of Sb 2 Se 3 . 18 We varied the doping level of the n-type surface layer from 10 13 to 10 19 cm –3 and the doping depth from 2 to 20 nm, while keeping other parameters constant, including the interface defect properties. As the exact characteristics of this doping layer are currently unknown, we performed a parametric variation of both doping level and depth simultaneously to create surface plots for each photovoltaic figure of merit.…”
Section: Resultsmentioning
confidence: 99%
“…This was experimentally confirmed by Mao et al in superstrate configuration Sb 2 (S,Se) 3 solar cells. Gon Medaille et al also demonstrate that either selective surface sulfurization or the introduction of a very thin Al 2 O 3 layer at the interface could also significantly reduce the interface recombination, boosting the efficiency of the devices . Experimentally, Feng et al reported an efficiency enhancement by adding an ultrathin (between 0.1 and 2 nm) Si 3 N 4 passivating layer between the absorber and the CdS layer in substrate configuration devices .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the variable J-V distortion observed in the present study, our previous work, and seemingly elsewhere in Sb 2 Se 3 literature with TiO 2 ETLs, a model of our device was constructed to allow for interrogation of the underlying device physics. The baseline Sb 2 Se 3 device model is adapted from Medaille et al, [92] which was defined using experimental data, and is detailed in Tables S4-S6 (Supporting Information).…”
Section: Device Simulationsmentioning
confidence: 99%